Large deviations for the numbers of occurrence of recurrent events - Aleškevičienė, A. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Алешкявичене. Большие уклонения для числа появлений рекуррентного событияA. Aleškevičienė. Didelių atsilenkimų teoremos rekurentinių įvykių pasirodymo skaičiui